2010
DOI: 10.4269/ajtmh.2010.10-0050
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multiplex Real-Time Polymerase Chain Reaction for Detection of Entamoeba histolytica, Entamoeba dispar, and Entamoeba moshkovskii in Clinical Specimens

Abstract: Abstract. Multiplex real -time polymerase chain reaction (PCR) was developed for differential detection of Entamoeba histolytica , Entamoeba dispar , and Entamoeba moshkovskii . Specific primers were designed for all three species, and then differentiation of E. histolytica and E. dispar was achieved simultaneously using a hybridization probe and melting curve analysis, whereas E. moshkovskii was detected with a separate probe under the same condition. This assay detected as little as 0.2 pg of E. histolytica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 24 publications
2
28
1
Order By: Relevance
“…However, since the recognition of the high prevalence of E moshkovskii in humans, 2 real-time PCRs have been developed to detect E histolytica, E dispar, and E moshkovskii in stool specimens. 30,31 There is currently no real-time PCR to detect E bangladeshi.…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the recognition of the high prevalence of E moshkovskii in humans, 2 real-time PCRs have been developed to detect E histolytica, E dispar, and E moshkovskii in stool specimens. 30,31 There is currently no real-time PCR to detect E bangladeshi.…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…9 Since then, human isolates of E moshkovskii have been reported from at least 13 other countries, including both resource-poor and resource-rich countries: the United States, Italy, South Africa, India, Australia, Pakistan, Iran, Tanzania, Turkey, Malaysia, Thailand, Tunisia, and the United Arab Emirates. 9,[21][22][23][24][25][26][27][28][29][30][31][32][33] In most of these studies the ameba has not been associated with disease and was isolated from very few individuals. However, high prevalences of E moshkovskii were reported in some countries: 50% in Australia, 23 24.9% and 15.6% in 2 different study populations in India, 34,35 21.1% in Bangladesh, 9 13.2% in Tanzania, 26 13.2% in Pakistan, 24 and 5.2% in Iran.…”
Section: Entamoeba Disparmentioning
confidence: 99%
“…We selected the 18s ribosomal gene for RPA because of its high copy number and because PCR studies have demonstrated its usefulness to distinguish Entamoeba species. [15][16][17] For the RPA reactions, we used a set of primers of 25 nt in size compatible with RPA assays that amplify specifically a 132 amplicon of E. histolytica but not E. dispar. We adapted the RPA for LF detection by using an internal duallabeled probe that allowed the specific detection of the amplicon on LF paper strips.…”
Section: Discussionmentioning
confidence: 99%
“…If there were sequential serologic data for E. histolytica infections, the method described in the current study could be used to estimate the prevalence. Because E. histolytica is morphologically indistinguishable from E. dispar, [28][29][30][31] an ELISA was used to investigate the seroprevalence of E. histolytica infections.…”
Section: Discussionmentioning
confidence: 99%